Estudo comparativo entre o tratamento radioterápico com elétrons e betaterapia após cirurgia de quelóide - Oliveira Júnior, Batista de [UNESP] (2007)
Keloids are common forms of abnormal scar resulting from abnormal responses to wounding that can originate after trauma or other injuries of the skin. They can be induced by surgery, tear, tattooing, burning, injection, bite, vaccine, as well as dematosis (supurative hydradenite) or foreign body reaction. Morfologicaly keloids are characterized by means of cellular hyperplasia, produced by intrinsecaly normal polyclonal fibroblasts that answer to abnormal extracelular signal. Keloid once a time formed is not radiosensitive, and in these circunstances the fibrotic tissue will suffer little or no change with radiation. On other side the ionizing irradiation can produce some degrees of regression in keloid just formed. The fibroblasts in a recent scar of an individual that forms keloid, are higly responsive. Recent keloids are rich in fibroblasts. Trott13 considered that the way of irradiation action in fibroblasts is based on the inhibition of proliferation and acceleration on differenciation of these cells. To the patients keloid is not only a cosmetic problem. Keloid scars can itch, hurt, as well as do some clothes intolerance, many times having more importance that the aesthetic aspect. The surgery alone has disappointed results, with recurrence rates in order of 50-80%. These results leadead a variety of treatments: criotherapy, laser therapy, intra lesional injection of cortisones and others. The modality that reached better results with minimum recurrence rates was percutaneous radiotherapy after surgery, with 2-36% of recurrence rates. After the 70's decade, the use of Sr90 (betatherapy) was diffused in keloids treatment, and some authors started the use of low energy electron beam with encouraging results and minimum side effects. Our study compared the use of Sr90 (betatherapy) with electron beam irradiation and we conclude... (Complete abstract click electronic access below)